Suplementação de L-carnitina e betaína para tilápias do Nilo - Sanchez, Milena Souza dos Santos (2018)
The objective of this study was to evaluate the productive, morphological and chemical composition, histology of the intestine, muscle and liver, hematology, biochemistry and enzymatic activity of Nile tilapia (Oreochromis niloticus) supplemented with L-carnitine. For this purpose, 144 tilapia with a mean weight of 27.76 ± 1.31g were randomly distributed in thee treatments, consisting of three levels of L-carnitine (500, 1000 and 2000 mg Kg-1 of feed) and control group. The fish distributed in 12 tanks of 0.45m3, adapted to a recirculation system, with controlled temperature and constant aeration. Experimental diets calculated to be isoenergetic (3200 kcal kg-1 ED) and isoproteic (28% PD). During the experimental period of 105 days the fish were fed four times a day and at the end of the experiment had their performance variables: weight gain (GP), daily weight gain (GPD), apparent feed conversion (CAA), rate (TEP), protein retention rate (TRE), protein retention rate (TRE), fillet (RF) yield and survival (SO). Morphological: hepatosomatic index (IHS) and fat somatic index (IGVS). Centesimals: moisture, protein, lipids and ashes. Histological: intestine, muscle and liver. Hematological, biochemical and enzymatic. ANOVA was applied to evaluate the best level of micronutrients inclusion and, when significant, the means were submitted to the Tukey test (P<0.05). Fish supplemented with 500 mg Kg-1 of L-carnitine presented increase of GP, GPD, TCE, RF and lower feed cost per kilogram of fish produced. In addition, fish also increased IHS, IGHS, fillet lipids, triglycerides, number of hepatocytes and greater activity of the enzyme catalase (CAT). Supplementation levels reduced fish microvilli, but did not affect the number of muscle fibers. Thus, it was determined that the supplementation of L-carnitine in proportions of 500 mg kg-1 of ration improves the performance and metabolic functions of tilapia.